2013
DOI: 10.1016/j.canlet.2012.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing in the clinic: Promises and challenges

Abstract: The advent of next generation sequencing (NGS) technologies has revolutionized the field of genomics, enabling fast and cost-effective generation of genome-scale sequence data with exquisite resolution and accuracy. Over the past years, rapid technological advances led by academic institutions and companies have continued to broaden NGS applications from research to the clinic. A recent crop of discoveries have highlighted the medical impact of NGS technologies on Mendelian and complex diseases, particularly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
210
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(215 citation statements)
references
References 194 publications
1
210
1
3
Order By: Relevance
“…These results are noteworthy because, to date, concerns have been widely expressed about the complexity, accuracy, and reproducibility of NGS for application in clinical trials. 17,18 Our results clearly indicate that locked and controlled procedures permit reliable, accurate, and reproducible use of NGS for clinical purposes. Reproducibility was found for variants known to exist in the specimen and across all reportable variants sites (MOIs), whether the allele was found or not on comparison to the human genome hg19 reference sequence.…”
Section: Discussionmentioning
confidence: 52%
“…These results are noteworthy because, to date, concerns have been widely expressed about the complexity, accuracy, and reproducibility of NGS for application in clinical trials. 17,18 Our results clearly indicate that locked and controlled procedures permit reliable, accurate, and reproducible use of NGS for clinical purposes. Reproducibility was found for variants known to exist in the specimen and across all reportable variants sites (MOIs), whether the allele was found or not on comparison to the human genome hg19 reference sequence.…”
Section: Discussionmentioning
confidence: 52%
“…Financial limitations have impaired the use of this technology beyond the research area. The advent of massive parallel DNA sequencing platforms, named next-generation sequencing (NGS) technology, has revolutionized the field of medical genomics, allowing fast and costeffective generation of genetic data [10]. The massive genetic screening has yet to fully enter the clinical field, hampered by the excess of generated genetic data, and specially the clinical phenotype interpretation.…”
Section: -Introductionmentioning
confidence: 99%
“…7 Currently, however, a large proportion of clinical NGS endeavors are supported by larger academic institutions with shared access to established genomic and bioinformatics research infrastructures, and routine clinical implementation of NGS is complicated by mitigating factors, such as clinical performance, laboratory expertise, lengthy turn-around times, and cost. 8 Thus, we investigated affordable methods to detect clinically relevant somatic mutations in NSCLC, melanoma, and gastrointestinal (GI) malignancies that generated high-quality sequencing data from FFPE samples, and offered manageable turn-around times. Targeted amplicon-based library preparation methods combined with parallel sequencing offered a practical solution, and recent studies have demonstrated the utility of this approach.…”
mentioning
confidence: 99%